Borrelia burgdorferi strain and host sex influence pathogen prevalence and abundance in the tissues of a laboratory rodent host. Issue 22 (27th September 2022) - Zinck, Christopher B.; Thampy, Prasobh Raveendran; Rego, Ryan O. M.; Brisson, Dustin; Ogden, Nicholas H.; Voordouw, Maarten
Abstract: Experimental infections with different pathogen strains give insight into pathogen life history traits. The purpose of the present study was to compare variation in tissue infection prevalence and spirochete abundance among strains of Borrelia burgdorferi in a rodent host ( Mus musculus, C3H/HeJ). Male and female mice were experimentally infected via tick bite with one of 12 strains. Ear tissue biopsies were taken at days 29, 59 and 89 postinfection, and seven tissues were collected at necropsy. The presence and abundance of spirochetes in the mouse tissues were measured by quantitative polymerase chain reaction. To determine the frequencies of our strains in nature, their multilocus sequence types were matched to published data sets. For the infected mice, 56.6% of the tissues were infected with B. burgdorferi . The mean spirochete load in the mouse necropsy tissues varied 4.8‐fold between the strains. The mean spirochete load in the ear tissue biopsies decreased rapidly over time for some strains. The percentage of infected tissues in male mice (65.4%) was significantly higher compared to female mice (50.5%). The mean spirochete load in the seven tissues was 1.5× higher in male mice compared to female mice; this male bias was 15.3× higher in the ventral skin. Across the 11 strains, the mean spirochete loads in the infected mouse tissues were positively correlated with the strain‐specific frequencies in their tick vector populations. The study suggests that laboratory‐based estimates of pathogen abundance in host tissues can predict the strain composition of this important tick‐borne pathogen in nature.